Factors Affecting Customers’ Motivation to Online Payment Systems in Bharatpur Metropolitan City (OCEM Journal of Management, Technology & Social Sciences, 2025)
Understanding the factors influencing online payment practices among undergraduate students in Nepal is imperative due to the country’s dependence on digital transactions and the changing financial technology landscape. This study aims to elucidate these factors in Bharatpur Metropolitan City, Chitwan District. This study seeks to comprehensively understand the opinions and experiences of undergraduate students regarding online payment practices by utilizing a quantitative approach. The sample population will consist of Two Hundred and Ten (N = 210) undergraduate students enrolled in BMC. The random sampling method is used to select the sample population. The ethical issues of this study were carefully considered during this research process.This study highlights mixed opinions on the usability and security of online payment platforms. Respondents expressed disbelief about users’ experience with payment systems’ transparency and security measures. Factors such as trust, service quality, and transaction fees shape online payment adoption, with some respondents voicing concerns about platform security and the adequacy of customer service.The findings of this study are expected to show associations between two factors and their impact on online payment practices. Key factors under examination include user experience, transaction fees, and user experiences in online payment systems.The implications of this study are far-reaching and extend to educational institutions, higher level students, researchers, organizational leaders, educators, new researchers, managers and young researchers alike. Insights gleaned from the study can inform policy decisions, academic interventions, and industry practices aimed at enhancing online payment practices and promoting financial literacy among undergraduate students in Nepal.